Evaluating the cost to industry of electricity outages - Hashemi, Majid; Jenkins, Glenn Paul; Jyoti, Roop; Ozbafli, Aygul (Taylor & Francis Inc, 2018)
The unreliability of electricity supplies is a major cause of the high cost of manufacturing in developing countries. In this paper, we propose a more accurate approach, the contribution method, to measure the cost imposed by power outages. We employ a rich, if not unique, set of data from the detailed operating accounts of three large manufacturing enterprises in Nepal. Estimating the true opportunity costs to the enterprises from lost production caused by power outages sheds light on the issue of cost measurement that is critical for the determination of the feasibility of mitigating measures. Furthermore, having such micro-based information on the value of lost load per kWh by firm or sector is critical for reducing the economic costs of planned outages by the electric utility.
Keywords: Electricity; industry; opportunity costs; outages; reliability